(untitled) (The Review of Diabetic Studies, 2025)
Leadership is a critical factor in retention and job satisfaction in nursing staff, particularly in a high-pressure environment such as a critical care department. This research paper set to evaluate the magnitude of transformational leadership and its effects on retention of nursing staffs and job satisfaction in critical care units in the Aseer Region of Saudi Arabia. The cross-sectional survey design was adopted, with the data being gathered with the help of 190 critical care nurses. Transformational leadership was also measured by the Transformational Leadership Questionnaire (TLQ) and the retention and job satisfaction of nursing staff were measured with the help of standardized scales. The researchers discovered that there were strong positive relationships between transformational leadership and nursing staff retention (r = 0.671) and job satisfaction (r = 0.596). The regression analysis showed that transformational leadership is a substantial factor that determines retention ( = 0.671) and job satisfaction ( = 0.596). There was no notable gender difference in the leadership styles, retention or satisfaction levels of the male and the female nurses. The results emphasize that transformational leadership can have a positive effect on nursing employees in critical care units in terms of staff retention and job satisfaction. Nurse retention and job satisfaction could be enhanced by improving practices of transformational leadership, which ultimately leads to an improvement in the quality of healthcare.